The Effect of Coordination on Employee Performance Through Communication at Pt PLN (PERSERO) UP 3 Langsa - Rambe, Saima; Dalimunte, Nurul; Erdin, Aldino (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study was conducted to determine the extent of the influence of coordination on employee performance through motivation at PT. PLN (Persero) UP3 Langsa, Where the study uses quantitative methods, namely data in the form of numbers or nominal with 4 variables, namely coordination (X1), Employee Performance (Y0 and Communication (Z), with a total of 43 respondents. Coordination partially has a positive and significant effect on Communication at the PT. PLN (Persero) UP3 Langsa Office. This can be seen from the t-count value of 14.476> t-table 2.019 and significant 0.000 <0.005. Coordination partially has a positive and significant effect on employee performance at the PT. PLN (Persero) UP3 Langsa Office. This can be seen from the t-count value of 3.055> t-table 2.021 and significant 0.004 <0.005. Coordination has a positive and significant effect on employee performance through Communication at the PT. PLN (Persero) UP3 Langsa Office. This is proven from the path analysis test which is known to have an indirect effect of 0.579 and greater than the direct influence of Coordination on employee performance, namely 0.344.